MEMBANGUN KOMUNIKASI YANG BAIK ANTAR SUAMI DAN ISTRI MELALUI MEDIA SOSIAL DALAM PERSPEKTIF EFESUS 4:29 - Muda, Stefanus (Jurnal Euntes, 2024)
Abstract Social media, as a tool or means of communication, provides benefits for married couples to connect, share everyday moments, and express feelings through digital platforms. However, social media also has negative impacts on communication between spouses. Therefore, in this article, the author encourages married couples to pay attention to every word when communicating through social media with each other. The author uses Ephesians 4:29 as both inspiration and reference, providing a theological foundation for married couples to be mindful of their words when communicating through social media, especially with each other. Through this article, the author hopes to help broaden the understanding of married couples, urging them to be attentive to their words in social media communication to avoid negative consequences that could lead to cracks in the relationship between spouses.